Analisis Laporan Arus Kas dalam Menilai Kinerja Keuangan Lembaga Keungan Syariah - Dewi Nur Fatmah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The cash flow statement is an essential component of financial reporting that provides information regarding the cash inflows and cash outflows of an entity during a specific period. In Islamic financial institutions, the cash flow statement is not only used to assess liquidity and financial performance but also serves as a monitoring instrument for ensuring Sharia compliance. This study aims to analyze the role of the cash flow statement in evaluating the financial performance of Islamic financial institutions and to examine its implementation based on Indonesian Islamic accounting standards. The research employs a normative legal research method using both a conceptual approach and a statutory approach. Data were collected through a literature review based on the Qur’an, Hadith, fatwas issued by the National Sharia Council of the Indonesian Ulema Council (DSN-MUI), Islamic Financial Accounting Standards (PSAK Syariah), books, and relevant scientific journals. The findings indicate that the cash flow statement performs a dual function: as a tool for evaluating financial performance and as an instrument to ensure that all cash receipt and disbursement activities are conducted in accordance with Sharia principles. An analysis of PSAK 101, PSAK 102, PSAK 105, and PSAK 106 demonstrates that Indonesian Islamic accounting standards provide adequate guidance for the presentation of cash flow statements based on Sharia contracts. This study contributes to strengthening the understanding that the cash flow statement is not solely oriented toward financial aspects but also serves as a means of promoting transparency, accountability, and Sharia compliance within Islamic financial institutions.